A Study on Factors Affecting Student’s Learning Soft Skills at Lac Hong University - Tran, Thị Kim Chi (Journal of Technical Education Science, 2022)
Training institutions, provide workers and students who will participate in the progress of the labour force found that: It is necessary to meet the needs of quality labourers at present, when; the integration door has been opening up a variety of job opportunities for workers. This also means that the recruitment criteria are higher, requiring the workforce, in addition to professional skills, to be equipped with soft skills, which are essential skills employers value. Researching the impact of factors affecting students' soft skills learning of LHU's students has 367 questionnaires whose researcher used in this report. The results have shown that there were six factors affecting students' soft skills learning which were "Training Courses", "Teaching Methods", "Lecturers", "Facilities", "Institution Policies", and "Practising Environment". Among these, "Facilities" strongly impacted students' soft skills learning.